2020
DOI: 10.1249/mss.0000000000002519
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Physiological Consequences of Low Energy Availability in a Male Combat Sport Athlete

Abstract: Medicine & Science in Sports & Exercise ® Published ahead of Print contains articles in unedited manuscript form that have been peer reviewed and accepted for publication. This manuscript will undergo copyediting, page composition, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered that could affect the content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…However, limitations include (1) assumption of specific tissue densities, which may differ in elite athletic populations; (2) residual lung volume can be a source of error, given an individual must exhale all of their air whilst remaining static for a stable value; (3) some individuals may become claustrophobic whilst underwater or not be comfortable in water; (4) the equipment is now uncommon and costly, whilst needing to be maintained, sterilised and cleaned regularly; (5) the technique cannot measure distribution of FFM or FM; (6) air can be contained within an individual’s swimsuit, skin, head, and/or body hair or internally such as in their digestive tract, all of which can be included in false estimations [ 6 ]; (7) air temperature, barometric pressure, nitrogen analyser and force sensor calibrations all contain sources of error, which could contribute to the overall measurement error [ 7 ]; and (8) is time consuming and potentially uncomfortable. Despite the fact that hydro-densitometry has long been considered a criterion assessment of body composition, the emergence of accurate surrogate techniques are now seen as more suitable alternates in applied sport [ 8 ] and in laboratory-based sport science research [ 9 , 10 , 11 ].…”
Section: An Overview Of Measurement Methodologies That Can Be Used In Applied Sport For the Assessment Of Body Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, limitations include (1) assumption of specific tissue densities, which may differ in elite athletic populations; (2) residual lung volume can be a source of error, given an individual must exhale all of their air whilst remaining static for a stable value; (3) some individuals may become claustrophobic whilst underwater or not be comfortable in water; (4) the equipment is now uncommon and costly, whilst needing to be maintained, sterilised and cleaned regularly; (5) the technique cannot measure distribution of FFM or FM; (6) air can be contained within an individual’s swimsuit, skin, head, and/or body hair or internally such as in their digestive tract, all of which can be included in false estimations [ 6 ]; (7) air temperature, barometric pressure, nitrogen analyser and force sensor calibrations all contain sources of error, which could contribute to the overall measurement error [ 7 ]; and (8) is time consuming and potentially uncomfortable. Despite the fact that hydro-densitometry has long been considered a criterion assessment of body composition, the emergence of accurate surrogate techniques are now seen as more suitable alternates in applied sport [ 8 ] and in laboratory-based sport science research [ 9 , 10 , 11 ].…”
Section: An Overview Of Measurement Methodologies That Can Be Used In Applied Sport For the Assessment Of Body Compositionmentioning
confidence: 99%
“…The major strength of DXA is the ability to measure BMC, which is growing in importance in due to the increasing awareness of low energy availability and the consequences of this on bone mineral content [ 70 ]. Furthermore, DXA provides limb-specific estimations of FM and FFM which can be useful when tracking injured athletes and the magnitude of fat loss in weight-making athletes [ 9 , 10 ].…”
Section: An Overview Of Measurement Methodologies That Can Be Used In Applied Sport For the Assessment Of Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woods et al (2017) reported reduction of ~2 kcal•kgFFM -1 •day -1 in RMR and body weight in elite rowers undertaking a 4-week intensified training period, without an apparent increase in EI. We recently reported a case study on a male combat athlete cutting weight for competition during 7 weeks of EA ~20 kcal•kgFFM -1 •day -1 and 1 week ~3 kcal•kgFFM -1 •day -1 , showing a clear concomitant decrease of RMRratio under 0.9 (Cunningham, 1980) and RED-S markers falling outside clinical reference ranges (Langan-Evans et al, 2020). Similarly, in the current study, we identified seven athletes (16%) with low RMR, five of whom had multiple other RED-S markers, such as subclinical low testosterone and fT3, subclinical high cortisol and elevated LDL.…”
Section: Prevalence Of Clustered Red-s Markersmentioning
confidence: 99%
“…Furthermore, when establishing EEE, consideration should also be given to appropriate calculation, whereby the other components of total energy expenditure (i.e. RMR and NEAT) are omitted during the time period of exercise [for a detailed description see Langan-Evans et al (2020)].…”
Section: Key Assessments For Weight Making Interventionsmentioning
confidence: 99%